Analysis of Student Ability in Answering Open Ended Final Exam Capita Selecta for Secondary Education Academic Year 2020/2021 - Hanifah Hanifah (Postgraduate, University of Mataram, 2023)
Capita Selecta Learning for Secondary Education for the 2020/2021 Academic Year takes place online by implementing the Project Based Learning Model (PjBl). This research aimed to determine students' abilities in designing learning scenarios using learning media on open exam questions. The research method used ex post facto. The subjects of this research were students of the Undergraduate Study Program Class A and Class B Semester V Mathematics Study Program FKIP UNIB for the 2020/2021 academic year who took the Capita Selecta Mathematics course. at secondary education level totaling 52 people. Research instruments are test sheet, answer sheet, and assessment sheet. The results of the research show that the average score for those who answered according to the task props = 58.85%, the average score for those who answered not according to the assignment props = 17.31% and the average score for those who did not answer = 23.85%. It can be concluded that more than 50% of them can design teacher and student conversations according to the task props in open-ended assignments. Based on the results of data processing, more than half of the students can think critically, creatively and communicatively.